Gerakan Agama Dan Politik Di Afrika Utara (Studi Terhadap Tokoh Muhammad Bin Tumart 515-526 H/1121-1130 M) - Sukmawati, Slamet; Otoman, Otoman (Tanjak: Sejarah dan Peradaban Islam, 2020)
Al-Muwahiddun Dynasty is an Islamic Dynasty in North Africa which was founded in 515 H/1121 AD, the founder of this dynasty was Muhammad bin Tumart through religious and political movements. This research tries to reveal the religious and political movements undertaken by Muhammad bin Tumart to rule North Africa. Data collection techniques from this study are in the form of book sources related to Muhammad bin Tumart and the Al-Muwahiddun Dynasty. This research uses qualitative data types with a historical approach and the theory uses role theory. This research reveals the religious and political movements undertaken by Muhammad bin Tumart to launch his ambition to overthrow the Al-Muwahiddun Dynasty and establish a new dynasty. To fulfil this ambition, he committed various religious deviations in order to attract sympathy for the tribes in North Africa to rebel from the rulers (Al-Murabithun Dynasty) and establish a new dynasty (Al-Muwahiddun Dynasty).